Analysis and Evaluation on the Use of Contemporary College English: Intensive Reading 2 (Third Edition) - Jang Xue (Pacific International Journal, 2024)
Teaching materials are a bridge connecting teachers, students and knowledge, and they play an irreplaceable role in ensuring the quality of education and promoting the all-round development of students. Among all the courses in the basic stage of English majors, the Integrated English Courses occupies a large proportion in the English majors’ curriculum. And the textbook for Integrated English 2, Contemporary College English: Intensive Reading 2, is widely used in colleges and universities in China. This study collected the data from questionnaire and interview to assess the Contemporary College English Intensive Reading 2 (Third Edition), in order to gauge student perceptions of its components and identify the textbook’s strengths, weaknesses, and usage challenges. The analysis indicates that while the textbook is largely effective in meeting educational goals and is appreciated for its content and organization, there are areas for improvement, particularly in the underuse of audio-visual resources and the need for differentiated support for students facing difficulties. To enhance the textbook, this study recommends the integration of AI in language learning, the use of interactive technologies, and the flipped classroom approach to foster a more dynamic and personalized learning experience. These adaptations aim to prepare English major students for modern challenges while maintaining the textbook’s relevance and efficacy.